Living together - Flowers, Mark; BBC Learning (Australia: BBC Learning, 2005)
This series visits the crucial moments in life's journey to dominate the earth.' Living together' revealed the relationship of predatory, competitive and cooperative among animals
Photography, Simon wagen ; executive producer, Michael Gunton ; series producer, Miles Barton
Keywords: Predatory animal